2017
DOI: 10.3390/w9110810
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Study on Extensive Green Roof Integrated Irrigation in Northwestern Arid Regions of China

Abstract: Selection of xerophils and drought tolerant plants is highly crucial in green roof techniques in the drought prone regions of Northwest China. In this study, the thermal performance under the natural conventional climate in summer was analyzed using a self-made simulation experimental platform through comparison of the internal surface temperature with and without green roofs. The distribution frequency of internal surface temperature was investigated by dividing internal surface temperature into several range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Latent heat losses through green roofs are associated with the evapotranspiration from plants and soil (Cascone et al, 2019), which largely depends on the water content of the roof (Santamouris, 2014). Previous studies suggested that the water content of green roofs largely influences their thermal performance; further, irrigation can improve the thermal performance of green roofs in dry regions (Feng et al, 2010;Sun et al, 2014;Wang et al, 2017). However, an experimental study conducted in Hong Kong (Jim & Peng, 2012) found that soil moisture had only a limited effect on the thermal performance of green roofs as evapotranspiration was predominately controlled by energy availability and not by water availability at their site, which was located in a humid region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Latent heat losses through green roofs are associated with the evapotranspiration from plants and soil (Cascone et al, 2019), which largely depends on the water content of the roof (Santamouris, 2014). Previous studies suggested that the water content of green roofs largely influences their thermal performance; further, irrigation can improve the thermal performance of green roofs in dry regions (Feng et al, 2010;Sun et al, 2014;Wang et al, 2017). However, an experimental study conducted in Hong Kong (Jim & Peng, 2012) found that soil moisture had only a limited effect on the thermal performance of green roofs as evapotranspiration was predominately controlled by energy availability and not by water availability at their site, which was located in a humid region.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term monitoring in New York City showed that white roofs could effectively maintain their temperature control effect for several years (Gaffin et al, 2012). Meanwhile, the cooling effects and energy saving potential of green roofs were shown through experiments and model simulations in cities, such as in Southern Italy (Brunetti et al, 2018), Chicago (Sharma et al, 2018), Toronto (Berardi, 2016), Hong Kong (Chan & Chow, 2013;Jim, 2014), and northwestern China (Wang et al, 2017). However, the answer to the question of which roof material has the best performance for mitigating the urban heat remains unclear, as relatively few studies have monitored and compared the temperature effects of different roof materials together.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another critical component is an irrigation system to manage the water supply to a green roof [38]. The irrigation system used for an extensive green roof consists of a reservoir (or a water tank), irrigation pipe, and water supply pump [39]. If the system tends to reuse the water, additional drainage pump and water collecting pipe is required.…”
Section: Green Roof Systemmentioning
confidence: 99%